Adherence to the Mediterranean diet and waist-to-hip ratio in middle-aged postmenopausal women are the main factors associated with semantic verbal fluency 12 years later - Rodriguez-Espinosa, Norberto; Moro Miguel, Adoración; Rodriguez-Perez, Maria del Cristo; Almeida-Gonzalez, Delia; Cabrera de Leon, Antonio (Frontiers in Nutrition, 2023)
Few studies have studied the effect of vascular risk factors and lifestyle habits affecting the middle age of postmenopausal women on later cognitive performance in old age. We have carried out an observational study to identify those factors and whether they differ from those acting in men. Postmenopausal women and males, both aged 40-60 years old at recruitment, from a community dwelling cohort were included. Data for this study were collected from the first visit at recruitment (2001 to 2005). Participants were interviewed with a questionnaire on their health-related antecedents and underwent a physical exam. The cohort was contacted again for a new presential visit between 2014 and 2015. A semantic verbal fluency test was included in this new visit protocol as a brief measure of cognition. Besides educational attainment, Mediterranean diet adherence 20th percentile (OR=1,93; 95%CI=1,07-3,47) and waist to hip ratio 80th percentile (OR=1,81; 95%CI=1,10-2,98) were the main factors associated to low semantic fluency performance in postmenopausal women, while declared diabetes mellitus (OR=2,24; 95%CI=1,16-4,33), HOMA 2 insulin resistance index (OR=1,77; 95%CI =1,04-3,02), light physical activity in leisure time (OR=0,41; 95%CI=0,19-0,93) and recommended moderate to vigorous physical activity (OR=2,09; 95%CI=1,23-3,56) did in men. Factors in middle age that explain semantic verbal fluency in old age are different between postmenopausal women and men. Menopause related fat redistribution may be a precondition for other vascular risk factors. The effect of Mediterranean diet on cognition deserves new specific studies centered on postmenopausal women as group.